2019
DOI: 10.46784/e-avm.v12i2.61
|View full text |Cite
|
Sign up to set email alerts
|

Notoedrosis in a Household Cat - Case Report

Abstract: Th is paper describes a rare case of severe notoedrosis (notoedric mange) in a household cat from the suburban region of Banja Luka, Bosnia and Herzegovina. According to history, the male cat was in direct contact with stray kitten which had dermatological disorder. Th e examination of the skin revealed an intensely pruritic and hyperkeratotic dermatitis with typical scabby appearance. Deep scarifi cation samples were collected from the altered skin area and macerated in 10% KOH. Th e microscopic examination r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Based on the morphology, circular body, small legs, with prolonged unjointed pedicels, with a short square rostrum, suckers on legs 1 and 2 and a dorsal anus, females are about 225μm in length and males about 150μm, the mites isolated were identified as Notoedres cati (Taylor et al 2015). On the other hand, the clinical manifestations observed as alopecia, erythema, scales, crusts, was and hyperkeratosis on the head and pinnae and malodorous from lesions is agreed with other reports (Reddy and Sivajothi 2014;Sivajothi et al 2015a;Ngetich 2019;Stevanović et al 2019). The application of products other than ivermectin has been shown to have positive effects on the recovery of the patient in feline scabies (Senthil et al 2008;Reddy and Sivajothi 2014;Sivajothi et al 2015b).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Based on the morphology, circular body, small legs, with prolonged unjointed pedicels, with a short square rostrum, suckers on legs 1 and 2 and a dorsal anus, females are about 225μm in length and males about 150μm, the mites isolated were identified as Notoedres cati (Taylor et al 2015). On the other hand, the clinical manifestations observed as alopecia, erythema, scales, crusts, was and hyperkeratosis on the head and pinnae and malodorous from lesions is agreed with other reports (Reddy and Sivajothi 2014;Sivajothi et al 2015a;Ngetich 2019;Stevanović et al 2019). The application of products other than ivermectin has been shown to have positive effects on the recovery of the patient in feline scabies (Senthil et al 2008;Reddy and Sivajothi 2014;Sivajothi et al 2015b).…”
Section: Discussionsupporting
confidence: 87%
“…The present study reports notoedric mange in a domestic short haired cat in Colombia. Several studies has been reported about notoedric mange in domestic cats (Sivajothi et al 2015b;Ngetich 2019;Stevanović et al 2019). Based on the morphology, circular body, small legs, with prolonged unjointed pedicels, with a short square rostrum, suckers on legs 1 and 2 and a dorsal anus, females are about 225μm in length and males about 150μm, the mites isolated were identified as Notoedres cati (Taylor et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize that a more comprehensive epizootiological examination is needed to determine the real distribution of sarcoptic mange in wild and domestic carnivores in our area. In Republic of Srpska, the presence of sarcoptides has been also confirmed -Notoedres cati in domestic cats (Stevanović et al, 2019).…”
Section: Figure 6 Sarcoptic Mange In the Fox -Autopsymentioning
confidence: 82%
“…Mites belonging to the genera Notoedres, Psoroptes, and Sarcoptes can be found in hedgehogs [12]. Notoedres cati and Otodectes cynotis have often been identified in hedgehogs and authors have suggested the contact with domestic cats as source of infection [3,[39][40][41][42]. Sarcoptes spp.…”
Section: External Parasitesmentioning
confidence: 99%